2015
DOI: 10.1155/2015/274607
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Serum Butyrylcholinesterase Activity Indicates Severe Systemic Inflammation in Critically Ill Patients

Abstract: Systemic inflammation is an immune response to a nonspecific insult of either infectious or noninfectious origin and remains a challenge in the intensive care units with high mortality rate. Cholinergic neurotransmission plays an important role in the regulation of the immune response during inflammation. We hypothesized that the activity of butyrylcholinesterase (BChE) might serve as a marker to identify and prognose systemic inflammation. By using a point-of-care-testing (POCT) approach we measured BChE acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 46 publications
3
62
4
Order By: Relevance
“…Reduced serum albumin concentration correlates with the increased mortality of critically ill patients 25,26. Previously, it has been shown that the BChE activity correlates with the albumin concentration in critically ill patients with severe systemic inflammation 7. However, in the present study, no correlation was observed between albumin concentration and the BChE activity in trauma patients.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Reduced serum albumin concentration correlates with the increased mortality of critically ill patients 25,26. Previously, it has been shown that the BChE activity correlates with the albumin concentration in critically ill patients with severe systemic inflammation 7. However, in the present study, no correlation was observed between albumin concentration and the BChE activity in trauma patients.…”
Section: Discussioncontrasting
confidence: 73%
“…Altered serum BChE activity might indicate a disrupted Ach hydrolysis, which would, in turn, indirectly signal an imbalance between the pro- and anti-inflammatory systemic responses mediated by nonneuronal cholinergic activity 4,6. Previously, it has been shown that patients diagnosed with severe systemic inflammation show a marked reduction in the activity of serum cholinesterase 7. However, due to the high variability in the onset and etiology of the observed conditions, it was difficult to determine whether the change in the enzyme activity correlated with the emergence of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these authors showed that a decrease in AChE-activity could be detected much earlier than other conventional laboratory tests generally used to diagnose sepsis (e.g. development of lactic acidosis) (22,36,37). The assumption that the decrease in AChE-activity is an early indicator of sepsis could not be con rmed in the results of the present study.…”
Section: Decrease Of Ache Activitycontrasting
confidence: 72%
“…The measurement of the AChE-activity is based on the modi ed Ellman method, a colorimetric method, improved by Worek et al (28). The literature based reference values of AChE-activity ranges from 26.7 U/gHb until 50.9 U/gHb (36,37). Due to a high inter-and intra-individual variability of AChE-activity, in clinical practice, a modi ed reference range from 30.0 to 50.0 U/gHb is more suitable (29).…”
Section: Ache-activity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation